The Impact of the Wae Ela Dam Flood Disaster on the Environment in Negeri Lima Village, Leihitu District, Central Maluku Regency. - Mahulauw, Ahmad Yasin; Lasaiba, Mohammad Amin; Riry, Roberth Berthy (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
This research discusses the social and economic impacts of natural disasters, particularly the flood caused by the breach of the Wae Ela Dam in Maluku. The research methodology employs a qualitative approach, collecting data through questionnaires, interviews, observations, and document analysis. The research respondents comprised 20 Negeri Lima Village households affected by the disaster. The research findings indicate that impacts involve changes in the community's livelihoods, job diversification, income, consumption patterns, and lifestyles. The implications of this disaster underscore the urgency of disaster prevention using instruments like the Environmental Impact Assessment. Collaboration between the government and the community in providing education on disaster mitigation and preparedness is crucial to mitigating disaster impacts.